The Global Findex Database 2021 : Financial Inclusion, Digital Payments, and Resilience in the Age of COVID-19 - Demirguc-Kunt, Asli; Klapper, Leora; Singer, Dorothe; Ansar, Saniya (Washington, DC: World Bank, 2022)
The fourth edition of Global Findex - the world's most comprehensive database on financial inclusion - offers a lens into how people accessed and used financial services during COVID-19, when mobility restrictions and health policies drove increased demand for digital services of all kinds.